Learning Mathematics in a Borderland Position: students' foregrounds and intentionality in a brazilian favela - Skovsmose, Ole; Scandiuzzi, Pedro Paulo [UNESP]; Valero, Paola; Alro, Helle (Unesp-dept Mathematica, 2012)
In a large metropolis, students from different neighbourhoods can experience very different life opportunities. This can influence their attitude towards schooling and learning, including the learning of mathematics. We interviewed a group of six students from a favela in a large city in the interior of the state of Sao Paulo in Brazil. We invited the students to look into their future and explore whether or not there could be learning motives that linked mathematics in school to possible out-of-school practices, either in terms of possible future jobs or further studies. We identified some themes in the students' descriptions of their experiences. The first theme is discrimination. The students feel discriminated against due to the fact that they come from a poor neighbourhood. They fear being trapped in some stereotypes. The second theme is escape. There is a strong motivation to begin a new life away from the favela. A third theme concerns the obscurity of mathematics. It seems clear to everybody that education is relevant to ensure a change in life. However, the mathematics lessons do not provide any clues regarding how mathematics might function is this respect. The fourth theme is uncertainty with respect to the future. The students could easily formulate almost unattainable aspirations, while reality might impose some very heavy limitations. In this article we introduce a theoretical framework for discussing the relation between favela students' life conditions in relation to their educational experiences and opportunities. Students' intentions for learning are related to their foregrounds, that is, how they perceive their future possibilities, as made evident to them by their social environment. Students in a favela could experience what we call a borderland position, a relational space where individuals meet their social environment and come to terms with the multiple choices that cultural and economic diversity make available to them.
Keywords: Borderland Position; Students' Foreground; Intentionality; Discrimination; Obscurity of Mathematics; Uncertainty with Respect to the Future